Pengaruh Dana Pihak Ketiga (DPK) dan Non-Performing Financing (NPF) Terhadap Profitabilitas Perbankan Syariah di Indonesia Tahun 2019-2024 - Zalzabila Aulya Irsya; Muhammad Ichwan Musa; Anwar; Anwar Ramli; Nurman (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to examine the impact of Third-Party Funds (DPK) and Non-Performing Financing (NPF) on profitability measured by Return on Assets (ROA) within the Indonesian sharia banking sector during the 2019–2024 period. A quantitative approach was employed using secondary data derived from the annual financial reports of 10 sharia banks in Indonesia. Purposive sampling was used to select the sample, resulting in a total of 60 observations. Panel data regression analysis was conducted using EViews software; based on the Chow, Hausman, and Lagrange Multiplier tests, the Random Effect Model (REM) was selected as the estimation model. The results indicate that, individually, DPK has a significant effect on ROA, whereas NPF has a significant negative effect on the ROA of sharia banks in Indonesia. Simultaneously, DPK and NPF exert a significant combined influence on ROA, with an R-squared value of 51.80%. These findings suggest that managing non-performing financing is a key factor in maintaining the profitability of sharia banks in Indonesia.